2020
DOI: 10.1111/1750-3841.15549
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolite profiling of liver in mice exposed to 2‐methylfuran

Abstract: Furan, a significant food contaminant, was found in many cooked foods. In most cooked foods, furan has been found to be coexisted with some alkylated derivatives such as 2‐methylfuran. 2‐methylfuran was found to be potent hepatotoxins. Little toxicological data is available for 2‐methylfuran. The objective of this study was to investigate metabolite changes in the liver samples from mice fed with 2‐methylfuran by untargeted metabolomic approach. Metabolomic analysis was conducted by using gas chromatography co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…And it was reported that cellular proline accumulation was a stress response because proline could scavenge free radical species. 32 Moreover, proline could transform into pyruvate to enter the citrate cycle, 33 which was related to energy metabolism in liver. The increase of valine and serine were as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…And it was reported that cellular proline accumulation was a stress response because proline could scavenge free radical species. 32 Moreover, proline could transform into pyruvate to enter the citrate cycle, 33 which was related to energy metabolism in liver. The increase of valine and serine were as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bisher Besonderheiten der Niere wurde jedoch nicht gesichtet (Gill et al, 2014). aminoacyl-tRNA (Hu et al, 2021).…”
Section: Exkretion Und Biomonitoringunclassified
“…Since the report published by the US Food and Drug Administration on the occurrence of furan in foods [ 5 ], it has become an increasing matter of concern and thus different aspects related to this compound have been studied. These aspects include mainly the toxicity [ 6 , 7 , 8 ], the formation pathways [ 9 , 10 , 11 ], the occurrence in foods [ 12 , 13 , 14 ], the risk assessment [ 15 , 16 , 17 , 18 ], and the analytics [ 19 , 20 ]. However, these data mainly refer to furan, while limited data are available on its alkyl derivatives.…”
Section: Introductionmentioning
confidence: 99%